حفیظ تائب کی نعتیہ شاعری میں قرآنی حوالے - Hamayoun, Dr. Zahid (Zoraiz, 2022)
Researchers agree on the fact that Na`at Started in Arabic Language in the very beginning. After the migration, all the non-Muslim poets started revilement against Hazarat Muhammad (S.A.W) thus Na’at poets started defending of prophet through Na`at poetry and this step grew in the shape of a school of thought. Some poets in that time used to narrate imaginary things they were inactive that’s why the Quran also condemned them and especially relates to the poets who worshiped Allah it is also said in the Quran that Allah and His angles say Darood-o-Salam on Muhammad (S.A.W) Hafeez Taib has fulfilled this duty in a beautiful manner through Na`at. He rejected the field of ghazal and has done great work while using Quranic allusions he used Quranic rhymes, Quranic Similes, and Quranic mataphors and gave the vast vision of Na`at subjects. He has also expanded Na`at in stylistic features. He has also done new experiments in the form of Na`at poetry by following the Quranic form of Surah-e-Kausar. He has given a great invention in the Na`at poetry triplet “Kousaria” which is different from other triplets. Hafeez Taib has a great study of the Quran that’s why we find the real soul of the Quran in his Na`at. Just because of the Quranic allusions we find a great level of knowledge and literature in his Na`at.